2019
DOI: 10.1093/heapol/czz075
|View full text |Cite
|
Sign up to set email alerts
|

‘Maternal deaths should simply be 0’: politicization of maternal death reporting and review processes in Ethiopia

Abstract: The Maternal Death Surveillance and Response system (MDSR) was implemented in Ethiopia in 2013 to record and review maternal deaths. The overall aim of the system is to identify and address gaps in order to prevent future death but, to date, around 10% of the expected number of deaths are reported. This article examines practices and reasoning involved in maternal death reporting and review practices in Ethiopia, building on the concept of ‘practical norms’. The study is based on multi-sited fieldwork at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 24 publications
(29 reference statements)
1
50
0
Order By: Relevance
“…In such environments, diverting accountability to factors out of control become the norm to avoid being blamed for poor outcomes. 8 Such situations have been reported in several death review practices. [9][10][11] Successful maternal death reviews require supportive political and policy environments, individual responsibility and ownership, a proactive institutional ethos, and promotion of learning as a crucial part of improving services and quality of care.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In such environments, diverting accountability to factors out of control become the norm to avoid being blamed for poor outcomes. 8 Such situations have been reported in several death review practices. [9][10][11] Successful maternal death reviews require supportive political and policy environments, individual responsibility and ownership, a proactive institutional ethos, and promotion of learning as a crucial part of improving services and quality of care.…”
Section: Introductionmentioning
confidence: 89%
“…20 Often, factors contributing to bad outcomes (deaths or delays) are stated to be the result of factors outside the control of local health workers and policy makers. 8,15 In a recent qualitative study of MDSR implementation in Ethiopia, Melberg et al showed that highly politicizing maternal deaths, as indicated by the common slogan of "no mother should die while giving birth" everywhere hinders the identification, reporting, review, or assignment of causes to maternal deaths. Health workers and officers leading MDSRs are under so much pressure to meet the political requirement of zero maternal deaths that there is a strong incentive to substantially underreport.…”
Section: Maternal Death Reviews In Ethiopiamentioning
confidence: 99%
See 3 more Smart Citations